Body Dissatisfaction, Perceived Gender Discrimination, Belief in a Just World, and Career-Choice Pessimism in Korean Female College Students: A Moderated Mediation Model - Kim, Eunha; Kwon, Min Hyuck (International Journal for the Advancement of Counselling, 2024)
Women’s body dissatisfaction is negatively associated with mental health and career-related outcomes. Despite the high prevalence of body dissatisfaction and dieting among younger South Korean adults, this relationship and its underlying mechanism remain underexamined. Therefore, we examined South Korean female college students’ body dissatisfaction, perceived gender discrimination, belief in a just world (BJW), and career-choice pessimism by testing a moderated mediation model. Body dissatisfaction was negatively related to BJW, but only at medium and high levels of perceived gender discrimination. Furthermore, we found support for a moderated mediation effect in which BJW mediated the relationship between body dissatisfaction and career-choice pessimism, but only at medium and high levels of perceived gender discrimination. These findings highlighted the relevance of body dissatisfaction and BJW to understand Korean female college students’ career-choice pessimism in the context of gender discrimination.
Keywords: Belief in a just world; Body dissatisfaction; Career-choice pessimism; Perceived gender discrimination; South Korea